1998
DOI: 10.1063/1.366902
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for proton motion in the recovery of light-induced degradation in amorphous silicon solar cells

Abstract: The light-induced degradation of amorphous silicon solar cells can be reversed by the application of a strong electric field in the dark, and the rate of reversal increases with field strength, temperature, and light intensity. The activation energy for annealing the degradation in the dark is reduced from about 1.34 eV under open circuit conditions to 1.16 eV by applying a strong reverse bias. When the degraded cells are exposed to intense illumination in addition to a strong reverse bias, the activation ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…4 shows the solar cell characteristics improve under reverse bias stress, and that the rate of such improvement increases with applied bias stress. So, we observe that the reverse bias stress rather than simply slowing down the wear out rate under light soaking [7,8], indeed improves the solar cell characteristics. We also observe that this effect weakly depends on the temperature during stress (see in Ref.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…4 shows the solar cell characteristics improve under reverse bias stress, and that the rate of such improvement increases with applied bias stress. So, we observe that the reverse bias stress rather than simply slowing down the wear out rate under light soaking [7,8], indeed improves the solar cell characteristics. We also observe that this effect weakly depends on the temperature during stress (see in Ref.…”
Section: Resultsmentioning
confidence: 85%
“…These works focus on the behaviour of the solar cell power conversion efficiency and fill factor. It was found that the rate of recovery of degradation depends strongly on the electric field, on the temperature and on the light intensity [7,8]. The authors suggested that their findings might be due to field emission of either electrons or holes from the metastable defects rendering these defects charged and therefore mobile or to hydrogen ion motion, possibly on the internal surfaces of micro voids.…”
Section: Introductionmentioning
confidence: 90%
“…Previous literature reported that the lightinduced degradation of a-Si:H cells could be recovered by applying large reverse bias. 10,11 By applying the reverse bias, the proton moves toward the p-layer of the top cell and then reacts with a Si dangling bond and a photo-generated electron to form a Si-H bond. The efficiency is recovered when the density of Si dangling bonds decreases.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] The light-induced degradation of a-Si:H cells can be recovered by applying strong reverse bias reportedly. 10,11 In this work, the recovery of the micromorph is investigated and a surprisingly low bias voltage is found for recovery.…”
mentioning
confidence: 99%
“…responsible for their creation. There is general consensus, however, that the hydrogen that plays a key role in eliminating dangling-bond defects in a-Si:H alloys also plays a key role in their light-induced creation (Lee et al, 1996;Carlson and Rajan, 1998). For a long time, the widely held view was that the only defect states produced by light were associated with the neutral dangling bond, D°.…”
Section: The Staebler-wronski Effectmentioning
confidence: 97%